2009
DOI: 10.3113/fai.2009.0891
|View full text |Cite
|
Sign up to set email alerts
|

Midfoot Charcot Arthropathy with Improvement of Arch after Achilles Tendon Lengthening: A Case Report

Abstract: Level of Evidence: V, Expert Opinion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Holthusen and Kolodziej found improvement in arch alignment after Achilles tendon lengthening in a patient with Charcot foot whose arch collapsed while in a total contact cast. 14 They felt Achilles lengthening can reduce deformity and ulceration in patients with Charcot foot. Mueller et al reported 81% (21/26) forefoot ulcer recurrence 2 years after healing with total contact casting alone but only 37% (10/27) recurrence if Achilles lengthening was added.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Holthusen and Kolodziej found improvement in arch alignment after Achilles tendon lengthening in a patient with Charcot foot whose arch collapsed while in a total contact cast. 14 They felt Achilles lengthening can reduce deformity and ulceration in patients with Charcot foot. Mueller et al reported 81% (21/26) forefoot ulcer recurrence 2 years after healing with total contact casting alone but only 37% (10/27) recurrence if Achilles lengthening was added.…”
Section: Discussionmentioning
confidence: 99%
“…10-12 Achilles tendon lengthening and GSR have been recommended as an adjunctive treatment for the Charcot foot. 1,2,5,9-11,13-15 Hastings et al showed that lengthening the Achilles tendon improved ankle dorsiflexion, decreased peak plantar pressures, and improved overall walking ability in a diabetic patient. 16 A systematic review of surgical management in Charcot foot patients gave lengthening of the Achilles tendon or gastrocnemius muscle a Grade B recommendation.…”
mentioning
confidence: 99%
“…A single case report has described radiographic improvement in arch height in an at-risk patient with CNA following TAL. 7 The purpose of the present study is to investigate the effectiveness of the TAL in those with midfoot collapse. We aim to quantify this in terms of average radiographic correction obtained across a series of patients.…”
Section: Introductionmentioning
confidence: 99%